Waste Management and Environmental Awareness Improvement Through Independent Community Service Program in Medan Krio Village - Willy Yusnandar (Jurnal Inovasi dan Pengabdian, 2025)
Medan Krio Village, with a relatively high population density, faces serious challenges related to waste management and low environmental awareness, often leading to environmental problems such as clogged drains and flooding. The Independent Community Service Program (KKN) aims to increase community understanding and participation in organic and non-organic waste management. The methods used include direct observation, community interviews, and outreach. The main program implemented included the creation of separate waste bins (organic and non-organic) and the socialization of the 3R concept (Reuse, Reduce, Recycle). The program also utilized plastic bottles to create unique piggy banks for students. The results showed that the program successfully established visible waste sorting facilities and provided practical education on recycling, instilling values ​​of creativity and savings habits in children. The KKN program has proven effective as a first step towards a cleaner and more sustainable village environment, although community awareness needs to be further enhanced.